KOSAKATA PROSESI MAKAN DALAM KELAMBU MASYARAKAT BUGIS DI SUNGAI KAKAP PENDEKATAN ETNOLINGUISTIK - Pribadi, Fajar Ary; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research deals with the field of linguistics. The research focuses on the Vocabulary of the Procession of Eating in the Bugis Mosquito Net in Sungai Kakap Ethnolinguistic Approach. Researchers use descriptive methods, qualitative research forms, and use ethnolinguistic approaches that look at the relationship of language with cultural elements in society. The analysis conducted by the researcher on the data collected includes the terms tools, materials, processes, and starting from the pre-implementation, implementation, and post-implementation analysis of the terms, namely monomorfemists, polymorphisms, and phrases. In addition, the researcher also analyzed the meaning of the terms in the lexical and cultural eating tradition in mosquito nets. This research succeeded in gathering 65 terms as research data. The whole data was obtained from the interview and recording process conducted by researchers in the District Kubu Raya, especially in the District Sungai Kakap Overall The data consists of 10 tool terms, 22 material terms, 29 process terms, 1 time term, and 3 place terms. Keywords: Eating in a Bugis Netting, Ethnolinguistics, Procession Vocabular.